The Analysis of Small Medium Enterprise’s Sukuk Investment Intention Through Financial Technology Securities Crowdfunding - Arief Luqman Hakim; Afif Zaerofi; Rahmat Mulyana (Institute for Research and Community Empowerment (LPPM TAZKIA), 2022)
The study is aimed at examining the determinants of retail investor to invest in small medium enterprise’s (SME) sukuk through Fintech Securities Crowdfunding (SCF) using the extended theory of planned behaviour (TPB). The cluster random sampling was applied and survey was conducted by distributing online questionairre to retail investors who already invested through SCF in Indonesia officially licensed by the OJK (Authority of Financial Services). The data of 218 respondent were analysed using SmartPLS 3.2.9. The result suggested that attitude, subjective norm and perceived behaviour control were statistically found significant to intention to invest in SME’s sukuk. The result also showed that other variables observed, knowledge, religious factor and risk & return have positively significant impact on attitude toward SME’s sukuk investment. Interestingly, sharia compliance factor not significantly impact to attitude.